Pengaruh Latihan Drill dan Berpasangan terhadap Ketepatan Passing Bawah pada Bola Voli Putri - Yulia Ratimiasih (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2021)
This study aims to determine the effect of drill and pair drills on the accuracy of under passing in the Ananta Club Women's Volleyball, Semarang Regency, and which exercise is more influential. The research method used is the accurate experimental method using a two groups pretest-posttest design. Sampling using a purposive side technique with the selection provisions, namely female, has been practicing at the Ananta club for at least one year, active and routinely exercising, has received down-passing material. The results showed that experiment I (drill group) with an average pretest score of 27.33 and an average posttest score of 32.50 with an average increase of 5.17. Experiment II (paired group) with an average pretest value of 28.33 and an average posttest value of 36.33 with an average increase of 8. The conclusion is that there is an effect of drill and pair training but paired training has more impact on the passing down in athletes women's volleyball club Ananta Semarang Regency. Keywords: Volleyball, Pair Practice, Drill Practice, Bottom Passing